Incidence, risk factors, and quality of life of low back pain after cesarean delivery and vaginal delivery at Dilla University General Hospital: a prospective cohort study - Barega, Muhiddin Tadesse; Hemba, Yadasa; Redela, Abdulfeta; Girma, Timsel; Milkiyas Wonte, Mesay; Dimma, Ali; Assen, Sofia; Eanga, Shamil (Frontiers in Medicine, 2025)
IntroductionLow back pain after delivery is a common and often debilitating condition that is frequently underdiagnosed and poorly managed. It is defined as discomfort or stiffness in the lower back. This study aimed to assess the incidence, risk factors, and quality of life associated with low back pain following vaginal and cesarean deliveries at Dilla University General Hospital in South Ethiopia from November 2021 to November 2022.MethodsA prospective cohort study was conducted on 129 pregnant mothers at Dilla University General Hospital. Demographic data and obstetric history were recorded before delivery. Postpartum data on the presence and severity of back pain were collected at multiple intervals from the first 24 h up to 6 months. The severity of back pain and quality of life were assessed by a numerical rating scale and the Short Form-36 health-related quality of life survey, respectively. Risk factors for postpartum low back pain were identified as significant at p < 0.05.ResultsThe incidence of low back pain was significantly higher in the cesarean delivery group compared to the vaginal delivery group from the second postpartum day to the fourth week (p < 0.05), but there were no significant differences between the groups on the first postpartum day or after a month. Most participants in both groups reported mild low back pain during follow-up. Body mass index over 30 kg/m2 [AOR = 3.01 (1.92–5.43), p = 0.013] and post-term gestation [AOR = 1.79 (1.23–7.75), p = 0.025] were identified as risk factors. Mothers who delivered via spontaneous vaginal delivery had a higher quality of life score (79.13 ± 7.06) compared to those who had a cesarean delivery (73.12 ± 3.46), with a p-value of 0.006 and an effect size of 0.48.ConclusionCesarean delivery is linked to a higher incidence of postpartum low back pain compared to spontaneous vaginal delivery from the second day to the fourth week after childbirth. A higher body mass index and post-term gestation were identified as risk factors. Additionally, the impact of low back pain on the quality of life accentuates the need for comprehensive postpartum care.